Screening and functional characterization of salt-tolerant NAC gene family members in Medicago sativa L - Li, Zhiguang; Yu, Qianqian; Ma, Yue; Miao, Fuhong; Ma, Lichao; Li, Shuo; Zhang, Huajie; Wang, Zeng-Yu; Yang, Guofeng; Su, Kunlong (Frontiers in Plant Science, 2025)
IntroductionAlfalfa is the most widely cultivated high-quality perennial leguminous forage crop in the world. In China, saline-alkali land represents an important yet underutilized land resource. Cultivating salt-tolerant alfalfa varieties is crucial for the effective development and utilization of saline-alkali soils and for promoting the sustainable growth of grassland-livestock farming in these regions. The NAC (NAM, ATAF, and CUC) family of transcription factors plays a key role in regulating gene expression in response to various abiotic stresses, such as drought, salinity and extreme temperatures, thereby enhancing plant stress tolerance.MethodsThis study evaluated the structure and evolutionary relationship of the members of the NAC-like transcription factor family in alfalfa using bioinformatics. We identified 114 members of the NAC gene family in the Zhongmu No.1 genome and classified them into 13 subclasses ranging from I to XIII. The bioinformatics analysis showed that subfamily V might be related to the response to salt stress. Gene expression analysis was conducted using RNA-seq and qRT-PCR, and MsNAC40 from subfamily V was chosen for further investigation into salt tolerance.ResultsMsNAC40 gene had an open reading frame of 990 bp and encoded a protein containing 329 amino acids, with a molecular weight of 3.70 KDa and a conserved NAM structural domain. The protein was hydrophilic with no transmembrane structure.After treating both the MsNAC40 overexpressing plants and the control group with 150 mmol/L NaCl for 15 days, physiological and biochemical measurements revealed that these plants had significantly greater height, net photosynthetic rate, stomatal conductance, and transpiration rate compared to the control group, while their conductivity was significantly lower. Additionally, the levels of abscisic acid in the roots and leaves, along with the activities of peroxidase, superoxide dismutase, and catalase in the leaves, were significantly higher in the overexpressing plants, whereas the malondialdehyde content was significantly lower. Moreover, the Na+ content in the overexpressing plants was significantly reduced, while the K+/Na+ ratio was significantly increased compared to the control group.DiscussionThese results indicated that the MsNAC40 gene improved the salt tolerance of Pioneer Alfalfa SY4D, but its potential mechanism of action still needs to be further explored.